2016
DOI: 10.1038/srep33144
|View full text |Cite
|
Sign up to set email alerts
|

Light-tunable Fano resonance in metal-dielectric multilayer structures

Abstract: High-Q optical Fano resonances realized in a variety of plasmonic nanostructures and metamaterials are very much promising for the development of new potent photonic devices, such as optical sensors and switches. One of the key issues in the development is to establish ways to effectively modulate the Fano resonance by external perturbations. Dynamic tuning of the Fano resonance applying the mechanical stress and electric fields has already been demonstrated. Here, we demonstrate another way of tuning, i.e., p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 42 publications
4
50
2
Order By: Relevance
“…The most popular approach to the excitation of Fano resonance in the mid‐infrared frequency range is to break the symmetry of metamaterial geometry . There are other methods including the multistacking of thin metal and dielectric layers and making use of material intrinsic damping as the subradiant mode . For example, with the mid‐infrared vibrational absorption resonance (phonon band) of silicon dioxide as the dark mode, the strong Fano coupling between the SiO 2 thin film and metamaterial split ring resonator (SRR) is observed such that it leads to mode splitting featured as frequency anticrossing .…”
Section: Introductionmentioning
confidence: 99%
“…The most popular approach to the excitation of Fano resonance in the mid‐infrared frequency range is to break the symmetry of metamaterial geometry . There are other methods including the multistacking of thin metal and dielectric layers and making use of material intrinsic damping as the subradiant mode . For example, with the mid‐infrared vibrational absorption resonance (phonon band) of silicon dioxide as the dark mode, the strong Fano coupling between the SiO 2 thin film and metamaterial split ring resonator (SRR) is observed such that it leads to mode splitting featured as frequency anticrossing .…”
Section: Introductionmentioning
confidence: 99%
“…26 Furthermore, we have demonstrated the light-tuning of the Fano resonance using a PMMA waveguide layer doped with photofunctional molecules (disperse red 1). 27,28 Very recently, Zheng et al 29 reported the results of experimental and numerical studies on the Fano resonance in a multilayer structure consisting of an Au layer, a SiO 2 layer, and a ZrO 2 layer surrounded by water.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the sharp Fano resonances provide a platform for achieving the high‐performance and ultrasmall optical modulators and switches. In the past decades, various tuning methods, such as the mechanical, thermal, magnetic, electrical, and optical tuning schemes, were utilized to improve the performance of the Fano modulators. All of these modulation approaches have applications in active plasmonic devices .…”
Section: Plasmonic Modulations Based On Fano Resonancesmentioning
confidence: 99%
“…However, because of the weak nonlinear light–matter interactions in natural materials and the short propagation distances of nanoscale‐confined SPP modes, the achievement of the all‐optical modulation with a large modulation depth in a small metallic nanostructure is an enormous challenge. The Fano resonances with sharp asymmetric profiles and strong field enhancements are extremely sensitive to the variations of the refractive index, and thus they provide an effective solution to this problem . By placing a photorefractive polymer on the metallic hole arrays, the Fano resonance (linewidth of Δλ ≈ 80 nm and spectral contrast of C ≈ 0.93) around λ = 750 nm was tuned based on the photorefractive effect under the pump beam of λ = 387 nm, as shown in Figure a .…”
Section: Plasmonic Modulations Based On Fano Resonancesmentioning
confidence: 99%
See 1 more Smart Citation